2019
DOI: 10.1002/ijc.32255
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the incidence and clearance of anal human papillomavirus infection among heterosexual men and women in Liuzhou, China: An observational cohort study

Abstract: Anal cancer is primarily caused by human papillomavirus (HPV) infection in both men and women. However, little is known about the sex differences in the natural history of anal HPV infection in a heterosexual population. From May 2014 to March 2016, perianal/anal canal (PA) swab samples were collected semiannually from 2,302 heterosexual men and 2,371 heterosexual women aged 18–55 years old in Liuzhou, China. The specimens were genotyped for HPV DNA by polymerase chain reaction. The incidence rate ratio (IRR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…In the same cohort in Liuzhou, we observed a longer persistence of any HPV type in both genital and anal sites in women compared with men (12,19). This observation is concordant with the data in the analysis we describe in this article, showing that the HRs of incident infection by any type of HPV seems higher in women who were positive for the same HPV type at the other site versus women who Figure 2.…”
Section: Discussionsupporting
confidence: 90%
“…In the same cohort in Liuzhou, we observed a longer persistence of any HPV type in both genital and anal sites in women compared with men (12,19). This observation is concordant with the data in the analysis we describe in this article, showing that the HRs of incident infection by any type of HPV seems higher in women who were positive for the same HPV type at the other site versus women who Figure 2.…”
Section: Discussionsupporting
confidence: 90%
“…HPV6 was also the genotype with lowest clearance rate (94.9/1000 pm) in a previous longitudinal study conducted among all men in a large Chinese city; however, clearance rates of most HPV genotypes in that study were much higher than those reported here. HPV 6 may be one of the most persistent genotypes in China, which could lead to a higher disease burden of anal warts [ 28 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that even if the HPV burden is low in men than women, this does not mean they are poor carriers of the virus. Indeed, Beachler et al reported that the clearance rate of HPV is lower in men, an idea not supported by studies carried out by Wei et al (31,32). However, considering the large number of samples obtained from 18 countries combined (>24,000 participants) and a relatively long period of observation in this study, it is reasonable to admit that men have a low clearance rate because they are less likely to develop natural anti-HPV immunity compared with women (33) who clear the infection within a relatively shorter period than men.…”
Section: Epidemiology Of Hpv Infection Worldwide and By Regionmentioning
confidence: 96%